Investigating Students’ Conception of Acid-Base Indicators Using Three Scientific Questions-Enhanced Conceptual Change Model - Rosalina Eka Permatasari; Suyono Suyono; Leny Yuanita (FKIP Universitas Lampung, 2024)
Investigating Students’ Conception of Acid-Base Indicators Using Three Scientific Questions-Enhanced Conceptual Change Model. Objectives:The aims of this research is to obtain the results of the analysis process and changes in students' conceptions on acid base indicators concept from the implementation of the conceptual change model enriched with three scientific questions (CCM-EWTSQ). The stages of CCM-EWTSQ are verification of misconceptions, creation of cognitive conflict conditions, providing assistance for equilibration, and reconstruction of final understanding. Methods: The research is using mixed methods which immersed quantitative research into qualitative research. The research subjects were students of the Chemistry Education Study Program, which consisted of four test students on the concept of acid-base indicators. The data obtained were analyzed descriptively qualitatively. Findings: The results of this study are as follows. Based on the results of two misconceptions verification, students found misconceptions about the concept of acid-base indicators (4 students). Each individual (research target) has undergone a process of changing cognition or conception in each stage of the CCM-EWTSQ on concept that students learn. The roadmap of changes in conception from stage to stage of CCM-EWTSQ experienced by each individual cannot be equated. The implementation of CCM-EWTSQ has succeeded in reducing the misconception of prospective chemistry teacher students who have verified misconceptions. Conclusion: Not all individuals who were verified had misconceptions at first and then turned into concept-aware after proceeding with CCM-EWTSQ Keywords: misconception, CCM-EWTSQ, CCMo, accommodation. DOI: http://dx.doi.org/10.23960/jpmipa/v25i1.pp341-350